A Test of the OPEC Cartel Hypothesis: 1974–1983 - LODERER, CLAUDIO (Journal of Finance, 1985)
ABSTRACT This paper tests whether the higher oil prices of the last decade could have been the result of producer collusion. We find little evidence that OPEC influenced oil prices during the years of skyrocketing prices (1974–1980), but there is evidence that it did so during the recent years of softening prices (1981–1983).